On quasi-periodic Baroclinic variability in the extratropical circulation - Crow, Brian, author; Thompson, David W. J., advisor; Barnes, Elizabeth A., committee member; Aster, Richard C., committee member (Colorado State University. Libraries, 2016)
A number of recent studies have demonstrated that large-scale extratropical wave activity is characterized by quasi-periodic behavior on timescales of 20-30 days, particularly in the Southern Hemisphere. This phenomenon has been termed the Baroclinic Annular Mode (BAM), and is responsible for the modulation of eddy heat fluxes, eddy kinetic energy, and precipitation on large scales. However, the extent to which this periodic modulation is discernable or significant on smaller spatial scales had not yet been established. Using data from the ECMWF Interim Reanalysis for the period 1979-2014, this study extensively examines the spatial structure of the BAM. Spectral analyses reveal the spatial limitations of the periodic behavior, while lag-correlation analyses reveal the patterns of propagation and development of anomalies that give rise to the observed periodicity. Periodic behavior is more robust in the Southern Hemisphere than in the Northern Hemisphere, but filtering out low wavenumbers from NH data helps clarify the BAM signal. Additionally, it is demonstrated that the BAM appears very differently in two relatively similar global climate models, suggesting further study is needed to determine how modern GCMs capture the BAM. Supplementing our analyses of observed and modeled data is a simple two-way linear feedback model, which is utilized to demonstrate the principal mechanism underlying periodic behavior in the BAM. The model makes it apparent that the BAM can be modeled as a simple linear feedback between baroclinicity and eddy heat fluxes. The periodicity seen on larger scales is a product of differential advection rates affecting the development of spatially overlapping, out-of-phase anomalies. The large-scale nature of the periodic behavior, however, makes it difficult to draw conclusions about the potential utility of the BAM for weather analysts and forecasters, and the limitations of this study limit our ability to describe its role in the climate system. It is hoped that the research presented here will pave the way to future studies which may more thoroughly answer such questions.
Keywords: extratropical circulation; atmospheric dynamics; weather and climate variability